2019
DOI: 10.2320/matertrans.mt-m2019145
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microstructure on Mechanical Properties of Harmonic Structure Designed Pure Ni

Abstract: This study aimed at investigating the influence of microstructure on mechanical properties of Harmonic Structured (HS) pure-Ni compacts. The harmonic structure is a heterogeneous microstructure with a spatial distribution of fine grains (FG) and coarse grains (CG), that is, the CG areas ('Core') embedded in the matrix of three-dimensionally continuously connected network of FG areas ('Shell'). The HS pure-Ni samples were fabricated by powder metallurgy route consisting of mechanical milling (MM) of plasma rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…However, it can be ensured that both MM and BiM powders show a bimodal microstructure wherein the center of powder is coarse-grained, whereas the surface composed of SPD sub-micron-sized grains. Similar morphological changes were also reported wherein it was observed that the increase in milling time leads to the formation of the severely deformed layer, consisting of nano-crystallites, near the surface of the powders [33][34][35][36][37]. Moreover, it must be realized that a gradient of the degree of deformation exists in both BiM and MM processed powders, and the severity of the accumulated plastic strain decreases from the particle surface towards the center of the particles.…”
Section: Microstructure Of Bim and MM Processed Powderssupporting
confidence: 73%
See 1 more Smart Citation
“…However, it can be ensured that both MM and BiM powders show a bimodal microstructure wherein the center of powder is coarse-grained, whereas the surface composed of SPD sub-micron-sized grains. Similar morphological changes were also reported wherein it was observed that the increase in milling time leads to the formation of the severely deformed layer, consisting of nano-crystallites, near the surface of the powders [33][34][35][36][37]. Moreover, it must be realized that a gradient of the degree of deformation exists in both BiM and MM processed powders, and the severity of the accumulated plastic strain decreases from the particle surface towards the center of the particles.…”
Section: Microstructure Of Bim and MM Processed Powderssupporting
confidence: 73%
“…Figure 5 shows TEM micrographs near the shell region of the mechanically milled pure titanium powder with enlarged areas of selected rectangular areas indicated as A, B, and C. It could be observed that near to the surface, equiaxed grains (<20 nm) were observed whereas a layer of elongated grains was seen in the inner zones of the milled powder. The grain subdivision and rotation of those elongated grains led to the formation of equiaxed nano-grain structure in milled powder [30,33,[37][38][39][40][41].…”
Section: Microstructure Of Bim and MM Processed Powdersmentioning
confidence: 99%
“…In contrast, in harmonic structured materials, work hardening is higher and lasts longer, which delays the initiation of plastic instabilities, and leads to simultaneous high tensile strength and uniform elongation. The outstanding mechanical properties of harmonic structured materials have been demonstrated in various metallic materials [49,50,[157][158][159][160][161][162][163][164]. The concept of harmonic structural design to improve mechanical properties can be applied to virtually all types of metallic materials.…”
Section: Harmonic Structured Materialsmentioning
confidence: 99%
“…1) A successful structural design was proposed by Ameyama et al, who developed a novel bimodal-grained microstructure design called "harmonic structure" with good balance in strength and ductility in various metallic materials, such as copper, 2) steel, 3) titanium, 4,5) and nickel. 6) This is a three-dimensional heterogeneous microstructure, consisting of a coarse-grained region called "core" and a fine-grained surrounding region called "shell". Zhang et al demonstrated that SUS304L stainless steel with a bimodal grained microstructure has an optimal balance of strength and ductility in comparison to its homogenous fine-grained and coarse-grained counterparts.…”
Section: Introductionmentioning
confidence: 99%